2021
DOI: 10.1002/adfm.202010145
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Polyanionic 2D Nanosheets Functionalized Nanofibrous Stem Cell‐based Neural Scaffolds

Abstract: Because developed neural cells are no longer regenerative and proliferative, achieving neural regenerations by using induced pluripotent stem cells (IPS cells) for nerve diseases have recently attracted much attention. Since the IPS cells’ growth and differentiation can be manipulated by different physical and chemicals cues, scaffolds combining the beneficial nanostructures and extracellular matrix may become an ideal interface to promote IPS cells’ neural differentiation. In this work, a biocompatible and mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Therefore, ROS scavenging biocatalytic and antioxidant nanostructures can be used in implanted stem‐cell protection. [ 218,219 ] A previous study has utilized GO flakes to save and protect the implanted MSCs from loss of cell‐extracellular matrix (ECM) interaction induced by ROS, thus increasing the survival of MSCs ( Figure A). [ 220 ] First, they proved that ECM proteins absorbed on GO flakes induced the expression of integrin β1 for MSC adhesion to GO flakes and prevented apoptotic signaling.…”
Section: Representative Biotherapeutic Applications Of Ros Scavenging Nanostructuresmentioning
confidence: 99%
“…Therefore, ROS scavenging biocatalytic and antioxidant nanostructures can be used in implanted stem‐cell protection. [ 218,219 ] A previous study has utilized GO flakes to save and protect the implanted MSCs from loss of cell‐extracellular matrix (ECM) interaction induced by ROS, thus increasing the survival of MSCs ( Figure A). [ 220 ] First, they proved that ECM proteins absorbed on GO flakes induced the expression of integrin β1 for MSC adhesion to GO flakes and prevented apoptotic signaling.…”
Section: Representative Biotherapeutic Applications Of Ros Scavenging Nanostructuresmentioning
confidence: 99%
“…[14][15][16] During the last few years, a large number of ROSbased EnzNAs have been constructed based on carbon, [17][18][19] organic molecules, [20] metal, [14,21,22] metal compounds, [23][24][25][26] and meta-organic framework (MOF). [27,28] Recently, transition-metal-based enzymatic nanoagents (TM-EnzNAs) have been intensively explored due to the special d-orbital electron of transition metal, [29][30][31][32][33][34] which become powerful nanoplatforms and exciting research frontiers in constructing nextgeneration nanotherapeutics to combat drug-resistant tumor and bacteria. [32,35,36] Although several comprehensive reviews about EnzNA have been reported, some of them focused on the detailed materials and enzyme-like activities along with their biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 According to various immobilization methods of heparin, activating inert catheter materials such as polyurethane is a key issue for surface modification. A series of strategies have been performed to enrich the surface with active functional groups such as hydroxyl, amine, carboxyl or sulfhydryl groups, mainly including plasma treatment/polymerization, [24][25][26][27] surface grafting and silanization. [28][29][30][31][32] However, the application of these strategies involving multiple steps or specific devices remains controversial in terms of in vivo biocompatibility or clinical practice.…”
Section: Introductionmentioning
confidence: 99%